2018
DOI: 10.1136/archdischild-2018-315711
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia for mild neonatal encephalopathy: a systematic review and meta-analysis

Abstract: ObjectivesTo examine if therapeutic hypothermia reduces the composite outcome of death, moderate or severe disability at 18 months or more after mild neonatal encephalopathy (NE).Data sourceMEDLINE, Cochrane database, Scopus and ISI Web of Knowledge databases, using ‘hypoxic ischaemic encephalopathy’, ‘newborn’ and ‘hypothermia’, and ‘clinical trials’ as medical subject headings and terms. Manual search of the reference lists of all eligible articles and major review articles and additional data from the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 16 publications
0
37
0
2
Order By: Relevance
“…There are no RCTs on TH in this population, and data from studies including these neonates showed variable results. A recent systematic review showed that there is insufficient evidence for a beneficial role of TH in babies with mild NE [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are no RCTs on TH in this population, and data from studies including these neonates showed variable results. A recent systematic review showed that there is insufficient evidence for a beneficial role of TH in babies with mild NE [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study does not include a healthy control group or newborns with asphyxia or classified as mild HIE (Sarnat 1), as only newborns subjected to hypothermia treatment were included. There is risk of adverse neurodevelopmental outcome of mild HIE newborns, but, up to now, there is no evidence to support cooling in these babies, and therefore we consider that the study of the metabolic fingerprint of those infants in correlation with the clinical outcomes would be of interest [30]. Furthermore, metabolomic coverage could be increased by taking advantage of complementary methods and analytical platforms.…”
Section: Discussionmentioning
confidence: 99%
“…11 The only proven indication of therapeutic hypothermia in paediatric patients is neonatal encephalopathy. 12 Therapeutic hypothermia modalities in children Therapeutic hypothermia requires mechanical ventilation. Careful attention must be given to the induction and maintenance of hypothermia, sedation, indications and modalities of neuromuscular blockade, monitoring (body temperature, electroencephalography [EEG], anaesthetics), and rewarming modalities.…”
Section: Targeted Hypothermia Indicationsmentioning
confidence: 99%